CROSS-CULTURAL COMPARISONS OF YOUNG CHILDREN’S EARLY NUMERACY PERFORMANCE: EFFECTS OF AN EXPLICIT MIDPOINT ON NUMBER LINE PERFORMANCE FOR CANADIAN AND CHINESE-CANADIAN CHILDREN - Xu, Chang; LeFevre, Jo-Anne (Bordón. Revista de Pedagogía, 2018)
INTRODUCTION. Children’s ability to place numbers on a line, where only the endpoints are marked, is related to other aspects of their mathematical understanding. In the present research, we examined the effects of a midpoint reference (e.g., marking the location of 5 on a 0-10 number line) on young children’s performance (3- to 5-year-olds) on a number line task. METHOD. We compared children with shared educational experiences but different cultural backgrounds: Chinese-Canadian children (n = 47) and Canadian children whose parents were educated in Canada or elsewhere (n = 47). All children completed a standard condition with only the endpoints marked and a midpoint condition where a midpoint reference was presented on the number line. RESULTS. The early numeracy skills of Chinese-Canadian children were better than those of the other Canadian children. Chinese-Canadian children made more accurate number line estimates when a midpoint reference at 5 was provided compared to Canadian children whereas the groups did not differ on a standard number line (i.e., no midpoint).Cultural differences persisted when mothers’ education, children’s age, and kindergarten attendance were controlled. DISCUSSION. These results suggest that strong fundamental numeracy skills are related to children’s performance on novel and complex tasks, such as the number line. These findings also indicate that differences across cultural groups may be related to language of instruction, parents’ education, or differences in home activities and emphasize the importance of developing more comprehensive frameworks for interpreting cultural differences in mathematical performance.